SISTEM INFORMASI PENGARSIPAN SURAT MASUK DAN SURAT KELUAR PADA BADAN KEPENDUDUKAN KELUARGA BERENCANA NASIONAL ( BKKBN ) PROPINSI JAMBI - Mulyadi - (JURNAL AKADEMIKA)
The National Family Planning Board (BKKBN) of Jambi Province is a non-departmental government institution. In mail archiving systems still use manual systems, such as still using paper as the main archive, which is often difficult to find the file, often the archive was notfound because of the many archives that existed for many years.With incoming and outgoing mail applications can reduce the time spent in mail archiving and disposition, reduce paper use, minimize the chances of errors in recording, speed up the mail search process, facilitate the control of letter disposition, and easy to use. To connect each form and avoid data redundancy use Inter-Table Relation (RAT) and Entity Relationship Diagram (ERD) and Data Flow Diagram (DFD) to see system flow. In building this system used Microsoft Visual Basic 6.0 and SQL Server 2000 programming languages ​​asdatabase.